Pengaruh Pembelajaran Kooperatif Tipe Stad Berbantuan Multimedia Interaktif Terhadap Hasil Belajar Matematika Kelas IV di SD Muhammadiyah Bantaeng - Bau Tiara Hasmar; Andi Husniati; Kristiawati Kristiawati (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
The main problem in this research is the influence of STAD type cooperative learning assisted by interactive multimedia on fourth grade Mathematics learning outcomes at Bantaeng Muhammadiyah Elementary School. This research aims to determine the effect of STAD type cooperative learning on fourth grade Mathematics learning outcomes at Muhammadiyah Bantaeng Elementary School by implementing STAD type cooperative learning assisted by interactive multimedia. This type of research is a pre-experiment with a one group pretest and posttest design consisting of one class carried out in 4 meetings. The population in this study was all fourth grade students at SD Muhammadiyah Bantaeng consisting of 18 people, with 12 female students and 6 male students. The sampling method is using a saturated sample. Saturated sampling is a sampling technique, if all members of the population are used as samples. The results of the research show that the average value of student learning outcomes before implementing STAD Type Cooperative Learning Assisted by Interactive Multimedia was obtained with a score of 36.11 from 18 students. There were 3 students who completed and 15 students who did not complete with a standard deviation value of 25,469, while the average value of student learning outcomes after implementing STAD type cooperative learning assisted by interactive multimedia was obtained with a value of 93.89 from 18 students. There were 18 students who completed with a standard deviation value of 6,978. Based on hypothesis testing using the T test, if the sig value is smaller than 0.05, then there is an influence of variable x on variable y. After carrying out the T test, research results were obtained with a value of 0.002, which means 0.002 < 0.05, which means there is an influence.